Taxes, status goods, and piracy - Alessandro Balestrino (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the design of indirect redistributive taxation and of corrective taxation, as well as the formation of equilibrium indirect tax policies via a political process, in the presence of status goods, allowing for the possibility that illegal copies of those goods may be purchased on black markets (the phenomenon of piracy). Heavy taxation of status goods, despite the fact these are typically overconsumed, is not particularly favoured in a social welfare maximisation context, because the tax rate is highly distortionary, due to the presence of piracy. Corrective taxation, aimed at remedying the inefficiencies associated with the consumption externalities generated by the status goods, is made ineffective by piracy. In contrast with the normative results, the median voter model predicts an inefficiently large tax rate on status goods when piracy is widespread.
Keywords: H23; H26; D72; 330; social status; indirect taxes; corrective taxes; median voter; piracy; Luxusgut; Indirekte Steuer; Internalisierung externer Effekte; Produktpiraterie; Median Voter; Soziale Wohlfahrtsfunktion; Theorie